CLEMENTE MARCONI (ED.), THE OXFORD HANDBOOK OF GREEK AND ROMAN ART AND ARCHITECTURE - Xenia Pausan (Journal of Ancient History and Archaeology)
Clemente Marconi (ed.), The Oxford Handbook of Greek and Roman Art and Architecture, Oxford University Press, New York 2015.